Food handler's level of COVID-19 prevention practice and preparedness of food and drinking establishments to combat the pandemic in Eastern Ethiopia - Habte, Sisay; Debella, Adera; Abdeta, Tilahun; Birhanu, Abdi; Balis, Bikila; Eshetu, Bajrond; Bekele, Habtamu (Frontiers in Public Health, 2022)
Background: Food and drinking establishments are potential hotspots for the spread of coronavirus. Food handlers have a higher risk of contracting the disease and transmitting it to others. This study was aimed to assess food handler’s level of preventive practice toward COVID-19 and preparedness of food and drinking establishments to tackle the pandemic in Eastern Ethiopia. Methods: Cross-sectional study was conducted from September 1 to 30, 2020. A stratified random sampling technique was utilized to select 276 licensed public food and drinking establishments and a simple random sampling technique was employed to select 422 food handlers from the selected establishments. Data were collected with a face-to-face interview and checklist-based observation. The collected data were entered into Epidata 3.2 and exported to STATA Version 16 for analysis. Binary logistic regression analyses were carried out to identify associated factors. Statistical significance was declared at P<0.05. Result: About 406 food handlers participated in this study making the response rate 96.2%. The study showed 38.4% of study participants (95% CI: 33.5, 43.1) had good preventive practices toward COVID-19. Only 11% of food and drinking establishments had fulfilled all requirements to prevent COVID-19 transmission. Being male [0.61 (CI: 0.39, 0.93)], Educational status, (attending secondary education [2.20 (CI: 1.37, 3.53)], having a favorable attitude about COVID 19 [1.89 (CI: 1.22, 2.95)], and good knowledge about COVID 19[1.78 (CI: 1.13, 2.81)] were significantly associated with the level of preventive practices towards Covid-19. Conclusion: The level of good COVID-19 preventive practice was only reported by less than half of study participants. Only one in ten food and drink establishments were fulfilled the national guideline for preventing COVID-19 transmission. Sex, educational status, knowledge of COVID-19, and attitude towards COVID-19 were significantly associated with good COVID-19 preventive practice. A vibrant guideline on prevention practices should be in place at all establishments, and compliance should be monitored. Local health office experts should take comprehensive measures, to make all food and drinking establishment accountable to practice all preventive measures.